Potential and Possible Ways of Harmonizing the Personal Income Taxation Process - Tomasz Wołowiec (Comparative Economic Research. Central and Eastern Europe, 2018)
Personal income tax (hereinafter referred to as PIT) has a short history, as it appeared in tax systems of EU countries as late as at the end of the 18th century. As a specific universal structure it performs two economic functions: providing financial means for covering some public expenses (fiscal function), leveling inequalities - through its structure - in population incomes (a redistribution function). It also implements social functions of taxation through various tax reliefs and exemptions or the structure of the tax scale. Contemporary personal income tax in European countries has been shaped by many years of evolution. This process is continuing, taking into account the process of European integration and the processes of standardizing and harmonizing tax systems in European Union countries. Most EU states only sporadically implement major reforms of personal income taxation. The scope of such changes is usually limited and determined by current fiscal needs or the need to stimulate a particular behavior of taxpayers. The current taxation of personal incomes is a very complex phenomenon which should be analyzed not only from the legal point of view, but also taking into account its social, cultural, economic and political system aspects.
Keywords: F15; H24; K34; 330; personal income taxation; EU integration; harmonization process; tax system; public finance